TEKNIK PEMANENAN MIKROALGA NANNOCHLOROPSIS sp. YANG DIKULTIVASI DALAM MEDIA LIMBAH CAIR KARET REMAH DENGAN FLOKULAN ALUMINIUM SULFAT [Harvesting Techniques Microalgae Nannochloropsis sp. Cultivated in Liquid Waste Rubber Crumb Media by AluminiumSulphate Floccullant] - Sri Hidayati; Otik Nawansih; Via Febiana (Jurnal Teknologi & Industri Hasil Pertanian, 2015)
This study was aimed to determine the best dosage for harvesting algaeusing Aluminium Sulfat. This research done by harvesting microalgae Nannochloropsis sp. which cultivated in the medium crumb rubber industrial wastewater (75% v/v) in an open reactor with a working volume of 5L for 8 days with flocculation methode using aluminium sulphate Al2(SO4)3 [H1] in dose of 50 , 100, 150, 200, 250, 300 mg/L, and 200 mg/L NaOH as a comparison (control). The results showed that microalgae Nannochloropsis sp. [H2] in the culivated medium crumb rubber industrial wastewater which was harvested using dose 150 mg/L of the flocculant agent aluminium sulphate Al2(SO4)3 [H3] by cell density 4055 x 104 sel/mL has the highest flocculation efficiency totalling 94,55%, dry biomass 0,7060 g/L, and oil content 23,24%.Keywords : Aluminium sulphate, Nannochloropsis sp, waste water